Metagenomic and whole-genome analysis reveals new lineages of gokushoviruses and biogeographic separation in the sea - Labonté, Jessica M.; Suttle, Curtis A. (Frontiers in Microbiology, 2013)
Much remains to be learned about single-stranded (ss) DNA viruses in natural systems, and the evolutionary relationships among them. One of the eight recognized families of ssDNA viruses is the Microviridae, a group of viruses infecting bacteria. In this study we used metagenomic analysis, genome assembly and amplicon sequencing of purified ssDNA to show that bacteriophages belonging to the subfamily Gokushovirinae within the Microviridae are genetically diverse and widespread members of marine microbial communities. Metagenomic analysis of coastal samples from the Gulf of Mexico and British Columbia, Canada, revealed numerous sequences belonging to gokushoviruses and allowed the assembly of five putative genomes with an organization similar to chlamydiamicroviruses. Fragment recruitment to these genomes from different metagenomic data sets is consistent with gokushovirus genotypes being restricted to specific oceanic regions. Conservation among the assembled genomes allowed the design of degenerate primers that target an 800 bp fragment from the gene encoding the major capsid protein. Sequences could be amplified from coastal temperate and subtropical waters, but not from samples collected from the Arctic Ocean, or freshwater lakes. Phylogenetic analysis revealed that most sequences were distantly related to those from cultured representatives. Moreover, the sequences fell into at least seven distinct evolutionary groups, most of which were represented by one of the assembled metagenomes. Our results greatly expand the known sequence space for gokushoviruses, and reveal biogeographic separation and new evolutionary lineages of gokushoviruses in the oceans.